Assessment of Unstimulated Whole Salivary Tumor Necrosis Factor Alpha (TNF-α) and Cellular Micronuclei Levels in Snuff (Naswar) Users and Non-Users for Early Diagnosis of Oral Squamous Cell Carcinoma - Muhammad, Waqar (Int J Environ Res Public Health, 2021)
The aim of the study was to investigate the unstimulated whole saliva (UWS) tumor necrosis factor alpha (TNF-α) and cellular micronuclei in snuff dippers (Naswar) compared to healthy control subjects. The case control study was conducted over 9 months at a tertiary care center. Sixty patients were divided into two groups: Snuff dippers (SD) (Naswar) and non-snuff dippers (NSD) (control subjects). The included self-reported SD used Snuff twice daily for more than 12 months. UWS was collected and salivary TNF-α assessment was performed using enzyme-linked immunosorbent assay (ELISA). For cellular micronuclei, buccal mucosa was brushed to obtain cells in Naswar users, fixed with a dibutylphthalate polystyrene xylene (DPX) mounting to view micronuclei. Means and standard deviations were compared using the t-test and outcomes were related using Pearson correlation, considering p ≤ 0.05 as significant. The mean age of participants was 38.85 ± 11.56 years. The mean duration of snuff use was 20.43 ± 12.79 years and the common site for Naswar placement was the lower vestibule (n = 19, 63.3%). TNF-α levels among SD were 9.6 ± 3.3 pg/mL, which were significantly higher than levels in NSD, 5.2 ± 3 pg/mL (p < 0.05). The number of cellular micronuclei in SD was 30.7 ± 7.8, which was comparatively higher than in NSD, which was 9.2 ± 3.3 (p < 0.05). The duration of snuff use was positively correlated to TNF-α levels (p = 0.048) rather than the micronuclei number (p = 0.97). SD showed higher levels of TNF-α and cellular micronuclei compared with NSD (control subjects); a positive correlation was shown with the duration of snuff use. We conclude that TNF-α and micronuclei are potential salivary biomarkers for an oral biological effect in snuff (Naswar) users.